Morphometric Analysis in Determining Body Score Index of Male Duroc Pigs - Kolo, Yuliana; Nubatonis, Alfred; Bria, Hendrikus Leonito; Boybana, Mekidius; Hakileu, Yohanes Rivandri; Bria, Siprianus Bere; Seran, Folgensius (JURNAL ILMIAH PETERNAKAN TERPADU, 2024)
This research aims to determine the index score of male Duroc pigs. The research was carried out at Mitra Tani Farm, Wewiku District, Malaka Regency. The livestock used in this research were 80 1 year old male Duroc pigs. The variable observed in this research is the Salako cumulative index which consists of weight index, height slope index, length index, width slope index, depth index, foreleg length index, balance and cumulative index which will be analyzed using the Salako (2006) formula to see the cumulative index to determine the index score of the livestock. The results of the study showed that the average morphometric size of male Duroc pigs was body weight 46.56 ± 24.00 kg, body length 58.43 ± 16.88 cm, shoulder height 50.78 ± 11.83 cm, hip height 52.00 ± 12.66 cm, chest circumference 77.90 ± 26.50 cm, chest width 18.45 ± 5.78 cm, chest depth 36.32 ± 12.95 cm, hip length 16.36 ± 4.67 cm, and hip width 12.28 ± 2.24 cm. The average weight index, height slope index, length index, width slope index, depth index, foreleg length index, and balance of male Duroc pigs from the research were respectively 14882.30 ± 8387.32; 1.23 ± 1.97; 1.14±0.13; 0.75±0.32; 0.70±0.14; 14.56±7.90; and 1.29 ± 0.70 with a cumulative index of 5.20 ± 2.35. Based on the research results obtained, it was concluded that the high cumulative index value of male pigs can be used to determine the body index score in livestock selection. This can be used as one of the selection criteria in improving the quality of pigs at Mitra Tani Farm Wewiku, Malaka Regency.